Catalysis by transition metal sulphides : from molecular theory to industrial application - Toulhoat, Hervé; Raybaud, Pascal (IFP énergies nouvelles publications., 2013)
The main application of transition metal sulphides as solid catalysts is for production of clean fuels in petroleum refineries. The various feedstocks to be processed all contain more or less sulphur, included in highly stable heteroaromatic molecules. In order to meet the stringent specifications imposed worldwide nowadays on transportation fuels to reduce their environmental impact, catalytic hydroprocessing remains essential. In this process, sulphur is removed as H2S following the reaction between molecular hydrogen and the heteroaromatics. This book aims to provide a complete, comprehensive, and updated survey of the field that will be useful to anyone involved; the student starting a research project, the academic researcher, or the refinery engineer will deepen their knowledge on the aspects of the catalytic process. Thirty-seven specialists from IFP Energies nouvelles, CNRS, and French universities have contributed, reporting a unique synthesis of the last fifteen years of research.